Fundamentals and considerations of the canine endometrial pathology - Sánchez Riquelme, Alfonso (2017)
The study of reproductive diseases is of great importance for clinical and medical approach. The aim of this article was to conduct a literature search on the grounds and considerations of canine endometrial pathology, with emphasis on endometrial cystic hyperplasia and pyometra, seeking support or refute the established concept or dogma, about the existing conditionality between them, which has been called cystic endometrial hyperplasia pyometra complex. According to the evidence, it is noted that there are two types of common uterine lesions in the bitch, that may occur independently: changes in growth pattern (hyperplasia) and inflammatory/infectious disorders (endometritispyometra). In the pathogenesis of both entities the role of progesterone, while generating cellular and molecular changes in the uterine epithelium, is indisputable.